2011
DOI: 10.1111/j.1741-1130.2011.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff Perspectives of Substance Use and Misuse Among Adults With Intellectual Disabilities Enrolled in Dutch Disability Services

Abstract: Although the use of psychoactive substances seems to be a growing problem among clients of intellectual disability services (IDS) in the Netherlands, rates of such substance use are unknown, and it is unclear how the services deal with substance‐related problems. This study explored the perspectives of staff with respect to the occurrence of substance use and abuse, as well as users' profiles, and service organization policies regarding substance use. A semi‐structured questionnaire asked staff to comment on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 7 publications
3
54
2
3
Order By: Relevance
“…Bransen and colleagues (2009) have shown that Dutch people with mild to borderline learning disability are more likely than young people in the general population to engage in binge drinking and heavy use of cannabis. Staff from 39 services for people with learning disability report that cannabis and other (illegal) drugs are used more often in comparison to the general population, whereas alcohol consumption was less (Van Der Nagel et al 2011). Estimations of harmful use or addiction for people with mild to borderline learning disability range from 15 percent to 42 precent (Kaal et al 2009;Tenneij and Koot 2006).…”
Section: Substance Use and Learning Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bransen and colleagues (2009) have shown that Dutch people with mild to borderline learning disability are more likely than young people in the general population to engage in binge drinking and heavy use of cannabis. Staff from 39 services for people with learning disability report that cannabis and other (illegal) drugs are used more often in comparison to the general population, whereas alcohol consumption was less (Van Der Nagel et al 2011). Estimations of harmful use or addiction for people with mild to borderline learning disability range from 15 percent to 42 precent (Kaal et al 2009;Tenneij and Koot 2006).…”
Section: Substance Use and Learning Disabilitymentioning
confidence: 99%
“…Estimations of harmful use or addiction for people with mild to borderline learning disability range from 15 percent to 42 precent (Kaal et al 2009;Tenneij and Koot 2006). People with learning disability are reported to be more vulnerable to the negative consequences of substance abuse, including victimization, dropping out of school or leaving work, psychiatric problems and other health-related problems Van Der Nagel et al 2011).…”
Section: Substance Use and Learning Disabilitymentioning
confidence: 99%
“…Many researchers found evidence that the prevalence of alcohol use was lower among adolescents with ID in comparison with adolescents without ID (Gress & Boss, 1996;McGillicuddy & Blane, 1999;McGuire et al, 2007;Pack et al, 1998;Rimmer et al, 1995;Robertson et al, 2000;Rurangirwa et al, 2006;VanDerNagel et al, 2011). However, Emerson and Turnbull (2005) reported a lower level of using alcohol at least once a month in adolescents with ID and no differences on lifetime alcohol use between adolescents with and without ID.…”
Section: Introductionmentioning
confidence: 85%
“…A Dutch study on substance use among the clients of ID services revealed that 79.1% of adolescents and adults had used alcohol (VanDerNagel, Kiewik, Buitelaar, & DeJong, 2011). In the UK study, Taggart, McLaughlin, Quinn, & Milligan (2006) revealed that alcohol was the most commonly used drug among individuals with ID.…”
Section: Introductionmentioning
confidence: 98%
“…Several demographic, contextual and diagnostic factors have been associated with SU(D) in MBID, such as younger than 30 years old, male, no structured daytime activities VanDerNagel et al 2011a), and living independently (Taggart et al 2006;To et al 2014). Furthermore, SU(D) in MBID is associated with psychiatric or behavioral (Chaplin et al 2011;Didden et al 2009) and forensic problems (Crocker et al 2007;Hassiotis et al 2011;Mcgillivray et al 2015).…”
Section: Introductionmentioning
confidence: 99%